DENTAL CARIES: CAUSES, MODERN TREATMENT, AND EFFECTIVE PREVENTIVE METHODS (International journal of artificial intelligence, 2025)
Dental caries is one of the most prevalent chronic diseases affecting individuals of all ages worldwide. It is a multifactorial condition primarily caused by the interaction of cariogenic bacteria, dietary sugars, and host susceptibility factors such as saliva composition and oral hygiene habits. Modern approaches to caries management emphasize early detection, minimally invasive treatment, and patient-centered preventive strategies. Effective preventive measures include proper oral hygiene practices, fluoride therapy, dietary modifications, sealants, and regular dental check-ups. This review highlights the etiology of dental caries, current treatment modalities, and evidence-based preventive strategies that can significantly reduce caries incidence and improve oral health outcomes.